Guidelines of community participation for sustainable tourism development : the case study of Tambon Cherngtaley, Amphur Thalang, Changwat Phuket - Nattamon Ratcharak (Prince of Songkla University, 2007)
Thesis (M.B.A., Hospitality and Tourism Management)--Prince of Songkla University, 2007